2017
DOI: 10.1155/2017/2450370
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Costs and Durations of Construction of Urban Roads Using ANN and SVM

Abstract: Offer preparation has always been a specific part of a building process which has significant impact on company business. Due to the fact that income greatly depends on offer’s precision and the balance between planned costs, both direct and overheads, and wished profit, it is necessary to prepare a precise offer within required time and available resources which are always insufficient. The paper presents a research of precision that can be achieved while using artificial intelligence for estimation of cost a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 51 publications
(54 reference statements)
1
48
0
Order By: Relevance
“…Third, based on the case studies applied to local office buildings, the accuracy and validity of the developed model was verified by comparison analysis between the actual construction duration and the predicted construction duration calculated from an approximate construction duration prediction model. Generally, the construction duration for office buildings are determined in two ways: the owner defines the project duration directly (Jin et al 2016;Bayram 2017;Peško et al 2017) or the contractor suggests construction duration to the owner. On the other hand, the construction duration computation model utilized by contractors during the project planning stage (Table 1) is not a specialized standard for general office buildings Koo et al 2010;Jin et al 2016;Kim et al 2016;Thomas, N., Thomas, A. V. 2016).…”
Section: Scope and Methods Of The Studymentioning
confidence: 99%
“…Third, based on the case studies applied to local office buildings, the accuracy and validity of the developed model was verified by comparison analysis between the actual construction duration and the predicted construction duration calculated from an approximate construction duration prediction model. Generally, the construction duration for office buildings are determined in two ways: the owner defines the project duration directly (Jin et al 2016;Bayram 2017;Peško et al 2017) or the contractor suggests construction duration to the owner. On the other hand, the construction duration computation model utilized by contractors during the project planning stage (Table 1) is not a specialized standard for general office buildings Koo et al 2010;Jin et al 2016;Kim et al 2016;Thomas, N., Thomas, A. V. 2016).…”
Section: Scope and Methods Of The Studymentioning
confidence: 99%
“…Despite the milestone achieved in this study, the regression model does not consider the mean square error associated with forecasting, which is solved in our proposed model. Peško et al proposed an artificial intelligence system for the approximation of duration and cost of a construction project [4]. The balance between the planned costs, overheads and direct cost considerably affect the prospected profits there; it is essential to prepare a consice offer for the available resources and the required time [4].…”
Section: Related Workmentioning
confidence: 99%
“…Studies have shown a profound discrepancy between the prospected duration and cost of a project and the real cost and duration, i.e., defines the actual project completion parameters [4]. The figures in these researches have demonstrated that it is vital for construction companies to create internal databases to be used as benchmarks for future projects.…”
Section: Introductionmentioning
confidence: 99%
“…In medicine, there is a study where ANNs where used to identify patients with hard risk for dying after suffering an acute myocardial infarction [35]. Furthermore, Pesko et al present a comparative study between the use of ANNs and support vector machines, which are used to estimate costs and duration time of the construction of urban roads [36].…”
Section: Complexitymentioning
confidence: 99%